DIGITAL LITERACY AMONG CHILDREN IN ELEMENTARY SCHOOLS - Hario Bismo Kuntarto; Amit Prakash (Mediakom, 2020)
The use of digital devices by children is on the rise and a better understanding of their usage behaviour can be helpful in designing better ways of imparting education. As per data from the Indonesia Internet Service Provider Association (APJII), in 2018, almost 50% of elementary school children were using the internet. However, an introduction to digital technologies is not included under the topics covered in state elementary schools in Indonesia. Field work involving teachers and children in state and non-state elementary schools, officials in ministries, ICT vendors, parents were conducted through interviews, observations and workshops related to the use of digital technology to better understand the digital behaviour of children. It was found that elementary school children get exposed to digital technology at a very early age and while the duration of use varies according to parental involvement and awareness, the content consumed by children is, in most cases, not appropriate for their age. This study illustrates that monitoring digital use among children is currently a challenge for parents, and digital literacy, which includes introduction to both positive and negative effects of digital devices as well as appropriate digital use behaviour, should become an important part of the theme of learning in elementary schools in Indonesia to ensure digital technologies help in the shaping of children's attitudes and character, in a manner that is valued and beneficial to the society. Kata Kunci: literasi digital, pemanfaatan digital oleh anak sekolah dasar, pengenalan digital pada anak Abstract – Use of digital devices by children is on the rise and a better understanding of their usage behaviour can be helpful in designing better ways of imparting education. As per data from the Indonesia Internet Service Provider Association (APJII), in 2018, almost 50% of elementary school children were using the internet. However, an introduction to digital technologies is not included under the topics covered in state elementary schools in Indonesia. Field work involving teachers and children in state and non-state elementary schools, officials in ministries, ICT vendors, parents were conducted over a six-month study period to better understand the digital behaviour of children. It was found that elementary school children get exposed to digital technology at a very early age and while the duration of use varies according to parental involvement and awareness, the content consumed by children is, in most cases, not appropriate for their age. This study illustrates that monitoring digital use among children is currently a challenge for parents, and digital literacy, which includes introduction to both positive and negative effects of digital devices as well as appropriate digital use behaviour, should become an important part of the theme of learning in elementary schools in Indonesia to ensure digital technologies help in the shaping of children's attitudes and character, in a manner that is valued and beneficial to the society.